Compression and energy absorption characteristics of additively manufactured reticulated tubes filled with spherical reticulated shells under axial crushing. (15th May 2022) - Wu, Fei; Chen, Yating; Zhao, Shunqiu; Zhang, Zhengrong; Zheng, Shiwei
Abstract: In this study, the concept of energy absorption and collision avoidance of metal tubes in the transportation field is combined with a spherical reticulated shell structure with excellent vibration absorption and impact resistance in the construction field. New energy absorption structures—reticulated tubes (RTs), equator skeleton spherical reticulated shells (ESs), truss spherical reticulated shells (TRs), and thin-walled sphere with round holes (TSHs), sphere-filled RTs, and sphere-filled thin-walled tubes—are proposed. For comparison, aluminium alloy thin-walled tubes and hollow spheres (HSs) are also included in the study. The HS, TSH, ES, and TR-filled RTs can produce more prominent filling effect than the corresponding aluminium alloy tubes and significantly improve the carrying capacity, energy absorption, crushing force efficiency, and specific energy absorption. Specifically, the filled RTs not only reduce the impact effect more notably and keep the initial impact peak almost unchanged but also significantly increase the energy absorption energy per unit mass compared to the filled aluminium alloy tubes. Thus, the HS, TSH, ES, and TR-filled RTs can be new types of lightweight structures which can meet the requirements of light weight, high energy absorption, and low impact effect.